Membentuk Karakter Melalui Moderasi Beragama Dengan Pendekatan Huruf Hijaiyah - Mahfudzi, Mahfudzi (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2021)
Studying the Science of Religion has different characteristics and levels of difficulty from studying general science, because studying the Science of Religion does not only emphasize mastery of material/cognitive/IQ alone, but it must also be able to instill attitudes of Spiritual/SQ intelligence and Emotional intelligence (EQ) simultaneously. Therefore, religious knowledge claimants must be able and willing to plan and formulate effective and efficient learning strategies and models so as to be able to shape spiritual attitudes and social attitudes.The reality is that learning Religion is carried out repeatedly starting from elementary school and equivalent, junior high school and equivalent, high school and up to tertiary level, but the knowledge is sometimes not in line with his actions, in other terms it is often referred to as intellectual arrogance. which is a self-righteous attitude. Therefore it is necessary to inculcate a creative and innovative attitude from someone to study the science of religion to its roots in order to improve the learning outcomes of religious knowledge which can provide an explanation of the meaningfulness of religious knowledge in daily life or religious moderation